2021
DOI: 10.15252/emmm.202012871
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of cell state changes in lung fibrosis with peripheral protein biomarkers

Abstract: The correspondence of cell state changes in diseased organs to peripheral protein signatures is currently unknown. Here, we generated and integrated single‐cell transcriptomic and proteomic data from multiple large pulmonary fibrosis patient cohorts. Integration of 233,638 single‐cell transcriptomes (n = 61) across three independent cohorts enabled us to derive shifts in cell type proportions and a robust core set of genes altered in lung fibrosis for 45 cell types. Mass spectrometry analysis of lung lavage fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 85 publications
3
71
0
Order By: Relevance
“…The power of large-scale single-cell cross-dataset analysis has been demonstrated in several recent studies [9][10][11][12][13][14][15] . We previously performed the first single-cell meta-analysis of the respiratory system, aggregating expression data of three genes important for SARS-CoV-2 cell entry from 31 datasets, spanning over 200 individuals 11 .…”
Section: Introductionmentioning
confidence: 98%
“…The power of large-scale single-cell cross-dataset analysis has been demonstrated in several recent studies [9][10][11][12][13][14][15] . We previously performed the first single-cell meta-analysis of the respiratory system, aggregating expression data of three genes important for SARS-CoV-2 cell entry from 31 datasets, spanning over 200 individuals 11 .…”
Section: Introductionmentioning
confidence: 98%
“…Subsequently, in order to further increase data resolution, we have pinpointed marker genes of all pathology-originating cells compared to healthy donated ones, as integrated by Mayr et al 13 . Pathology versus healthy state comparisons were performed for over 40 cell types’ top variable genes, resulting in an expression profiling of ten different pulmonary diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Last, in order to combine the better established methods of bulk DEA with the higher resolution of single cell data, Gene explorer maps each requested gene to single cell datasets of NU-Pulmonary cell browser in a species specific manner: human to Reyfman 27 and murine to Joshi-Watanabe 28 and Xie 29 datasets. More details on published scRNA-seq pulmonary fibrosis datasets can be found in the Single cell data tab of our web server, along with DEA results of Mayr et al dataset 13 in a tabular format. Please, refer to "Single cell data" section of the paper for more details.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kramann et al verified that perivascular Gli1+ MSC-like cells (i.e., pericytes) are one of the main sources of myofibroblasts in various organs by tracing their genetic lineage (Kramann et al, 2015). Based on that study, Mayr et al discovered a new pericyte state related to interstitial lung disease (ILD), namely, SSTR2+/CFHR1+ pericytes (somatostatin receptor two and complement factor H related 1) with high disease specificity, which have a proinflammatory phenotype and can express various chemokines (Mayr et al, 2021). It has been proven that pericytes separate from Ecs during chronic kidney injury and many studies have found that the separated pericytes show a tendency to differentiate into myofibroblasts (Bábíčková et al, 2017;Liu et al, 2018;Yamaguchi et al, 2020).…”
Section: Pericytesmentioning
confidence: 99%